Prevalencia de los defectos del habla en pacientes con maloclusiones dentales (2023)
The goal of this study is to establish the prevalence of dyslalias in patients diagnosed with dental malocclusions in the three planes of the space, attending the Orthodontic clinics of the Cooperative University of Colombia, Bogota, year 2012. A descriptive cross-sectional study was carried out in 68 patients diagnosed with dental malocclusion, by means of a clinical examination of the oral cavity, to evaluate the occlusal characteristics found in the sagittal, transverse and vertical planes applying the method of Bjork epidemiological record; they also recorded spontaneous narration with a TASCAM DR- 100MKIIR device, diagnosing the dyslalia according to the articulation point using the PHONR program for phonetic transcription. The results show that the most prevalent dyslalia was linguoalveolar (98.5%) followed by bilabial (7.4%) and linguodental (4.4%). All patients diagnosed with dyslalia had some type of malocclusion in the sagittal plane, class I (69.1%); in the vertical plane was the anterior open bite (25%), and in the transversal plane the crossbite (19.1%). Speech defects of syllables / cr /, / gr / and / pr / were related to class III malocclusion. The most disturbed sounds were the linguoalveolar (/ s / r / r /) and the syllables locked with / r /, suggesting malocclusions as a risk factor for the presence of dyslalias.